Heterozygous Kmt2d loss diminishes enhancers to render medulloblastoma cells vulnerable to combinatory inhibition of LSD1 and OXPHOS - Shilpa S. Dhar; Calena Brown; Ali Rizvi; Lauren Reed; Sivareddy Kotla; Constantin Zod; Janak Abraham; Jun-Ichi Abe; Veena Rajaram; Kaifu Chen; Min Gyu Lee (Cell Reports)
Summary: The histone H3 lysine 4 (H3K4) methyltransferase KMT2D (also called MLL4) is one of the most frequently mutated epigenetic modifiers in many cancers, including medulloblastoma (MB). Notably, heterozygous KMT2D loss frequently occurs in MB and other cancers. However, its oncogenic role remains largely uncharacterized. Here, we show that heterozygous Kmt2d loss in murine cerebellar regions promotes MB genesis driven by heterozygous loss of the MB-suppressor gene Ptch via the upregulation of tumor-promoting programs (e.g., oxidative phosphorylation [OXPHOS]). Downregulation of the transcription-repressive tumor suppressor NCOR2 by heterozygous Kmt2d loss, along with Ptch+/−-increased MYCN, upregulated tumor-promoting genes. Heterozygous Kmt2d loss substantially diminished enhancer marks (H3K4me1 and H3K27ac) and the H3K4me3 signature, including those for Ncor2. Combinatory pharmacological inhibition of the enhancer-decommissioning H3K4 demethylase LSD1 and OXPHOS significantly reduced the tumorigenicity of MB cells bearing heterozygous Kmt2d loss. Our findings suggest the molecular and epigenetic pathogenesis underlying the MB-promoting effect of heterozygous KMT2D loss.